The last racially separated church in the Dutch Reformed family of churches: Constituting the Synod of the Evangelical Reformed Church in Africa - Saayman, Willem (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
The author describes the history and circumstances around the founding of the last racially separated “daughter” church of the white Dutch Reformed Church (DRC), the Evangelical Reformed Church in Africa (ERCA) in Namibia in 1975. He places this in the context of racial and ethnic church formation by the DRC subsequent to the publication of the Tomlinson Report. The DRC in Namibia needed a black partner church in the north of Namibia in order to counter the alliance between Swapo and the Evangelical Lutheran Church of Ovambo-Kavango. ERCA was miniscule in size in comparison to the Lutheran and Roman Catholic churches in the northern “homelands” of Namibia, which was one reason why indigenous elders as well as some missionaries considered it unwise to institute a separate church at that time. The objections were overruled by the “mother” church (the DRC) that held the upper hand since it funded mission work in the northern “homelands”. The author concludes with some critical comments about this episode of DRC mission history.